Evidence from masked‐priming that initial identification of brand names is via abstract letter identities. (4th January 2019) - Martin, Nicholas; Davis, Colin J.
Abstract : Although visual‐word recognition is often assumed to proceed on the basis of case‐invariant letter representations, previous research has shown a role for letter‐case in recognizing brand names. One recent study reported early effects of letter‐case in a brand‐decision task using masked primes (Perea et al ., 2015, British Journal of Psychology, 106, 162). The present study attempts to replicate this finding using brand names typically presented in all lowercase (e.g., adidas), all uppercase (e.g., IKEA), or titlecase (e.g., Ford). Across three masked‐priming experiments, we found no advantage for case‐matched identity primes over case‐mismatched identity primes. This finding suggests that brand‐specific letter‐case information does not play a role in the early processing of brand names. However, we observed evidence that case may be used as a cue for making brand decisions, which may explain the effect reported by Perea et al . (2015, British Journal of Psychology, 106, 162).